1989
DOI: 10.1128/jb.171.9.4938-4944.1989
|View full text |Cite
|
Sign up to set email alerts
|

Translesion synthesis is the main component of SOS repair in bacteriophage lambda DNA

Abstract: Agents that interfere with DNA replication in Escherichia coli induce physiological adaptations that increase the probability of survival after DNA damage and the frequency of mutants among the survivors (the SOS response). Such agents also increase the survival rate and mutation frequency of irradiated bacteriophage after infection of treated bacteria, a phenomenon known as Weigle reactivation. In UV-irradiated single-stranded DNA phage, Weigle reactivation is thought to occur via induced, error-prone replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Despite several decades of vigorous exploration of T4 repair mechanisms, there is a striking absence of any report of the kind of break-reunion recombination repair so well characterized in E. coli. In phage , which relies upon E. coli repair systems, as many as 20 dimers/genome were insufficient to block viral DNA replication in an unirradiated, excision-deficient E. coli cell in which the recA-dependent recombination functions were not induced and in which few recombinational exchanges occurred (41). This high survival seems unlikely to have been simple translesion synthesis because there is little mutagenesis in UV light-irradiated phage in the absence of UV irradiation of the host (42); absent the induced level of classical recombination repair, the mechanism may have been replication repair.…”
Section: Discussionmentioning
confidence: 99%
“…Despite several decades of vigorous exploration of T4 repair mechanisms, there is a striking absence of any report of the kind of break-reunion recombination repair so well characterized in E. coli. In phage , which relies upon E. coli repair systems, as many as 20 dimers/genome were insufficient to block viral DNA replication in an unirradiated, excision-deficient E. coli cell in which the recA-dependent recombination functions were not induced and in which few recombinational exchanges occurred (41). This high survival seems unlikely to have been simple translesion synthesis because there is little mutagenesis in UV light-irradiated phage in the absence of UV irradiation of the host (42); absent the induced level of classical recombination repair, the mechanism may have been replication repair.…”
Section: Discussionmentioning
confidence: 99%
“…That is particularly significant for it shows that while nearly all the lethal lesions in dsDNA are repair- Ironically, the incorrect idea that dsDNA is more efficiently repaired by Weigle reactivation than ssDNA had the beneficial effect of stimulating an important study showing that recombinational repair contributes an insignificant amount to the SOS repair of UV-irradiated lambda relative to the contribution of translesion synthesis (5). Although an additional conclusion, namely, that inducible excision repair makes Weigle reactivation more efficient for dsDNA than for ssDNA, now appears to be unfounded, it should nevertheless prompt us to wonder why it is that Weigle reactivation is not more efficient for dsDNA.…”
mentioning
confidence: 99%
“…It has also been suggested that Weigle mutagenesis occurs in dsDNA with a higher efficiency than in ssDNA (4,5).…”
mentioning
confidence: 99%
“…Because the former mechanism could not be detected in yeast (Resnick, Boyce & Cox, 1981), and because proteins involved in T4 DNA transactions are more closely related to those in archaea and eukaryotes, it is possible that the eubacteria perform most of their recombination repair differently from organisms in the other two domains. It is also possible that E. coli does indeed carry out some replication repair, because inactivating the E. coli recA system still allows numerous lesions to be survived in phage (Defais et al, 1989), and because of ingenious genetic evidence that supports the operation of replication repair (Ozgenc, Szekeres & Lawrence, 2005).…”
Section: Replication Repairmentioning
confidence: 99%